PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, KEPEMILIKAN MANAJERIAL TERHADAP KINERJA PERUSAHAAN - Mukhamad Zaenal Abidin, 09.05.52.0067 (Students Journal of Accounting and Banking, 2013)
Stablishment of the company aims to improve the welfare of the shareholders. The good performance of the company will be able to give a better impact for shareholders. Companys performance can be measured by return on equity(ROE).This study aimed to examine the effect of capital structure, firm size and managerial ownership on firm performance.Population of this study are all companies listed on the Indonesia Stock Exchange (IDX) in 2012. Acquisition of data obtained from the Indonesian Capital Market Directory (ICMD) from 2009 to as many as 145 years 2011 manufacturing company. Types of data from this study is secondary data. Sample selection method used was purposive sampling. Data processing and analysis of data using multiple linear regression with SPSS version 16.0.These results indicate that the capital structure and significant positive effect on firm performance, firm size, and a significant positive effect on firm performance and managerial ownership and significant negative effect on firm performance. Test results produce the coefficient of determination adjusted R2 value is 0.094 this means 9.4% corporate performance variation can be explained by the variation of the three independent variables of capital structure, company size and ownership manajerial.sedangkan remaining 90.6% (100% - 9.4%) described by other variables outside our model..Keywords: capital structure, firm size, managerial ownership, corporate performance.